2021
DOI: 10.1002/dvdy.315
|View full text |Cite
|
Sign up to set email alerts
|

Lung injury in axolotl salamanders induces an organ‐wide proliferation response

Abstract: Background: Ambystoma mexicanum, the axolotl salamander, is a classic model organism used to study vertebrate regeneration. It is assumed that axolotls regenerate most tissues, but the exploration of lung regeneration has not been performed until now. Results: Unlike the blastema-based response used during appendage regeneration, lung amputation led to organ-wide proliferation. Pneumocytes and mesenchymal cells responded to injury by increased proliferation throughout the injured lung, which led to a recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…Limb amputation triggers cell-cycle activation in the contralateral, uninjured limbs, but also in other organs (Johnson et al, 2018). After a lung injury, a variety of cell types proliferate in the contralateral, uninjured lung (Jensen et al, 2021). In a regenerating tail, proliferating cells can be detected in the spinal cord as far as 5 mm away from the amputation site (Duerr et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limb amputation triggers cell-cycle activation in the contralateral, uninjured limbs, but also in other organs (Johnson et al, 2018). After a lung injury, a variety of cell types proliferate in the contralateral, uninjured lung (Jensen et al, 2021). In a regenerating tail, proliferating cells can be detected in the spinal cord as far as 5 mm away from the amputation site (Duerr et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Probes were also generated for Vimentin, Notch1, Jag1, Hes1 , and Hes5 . Probes were designed as described previously (Jensen et al, 2021), using Oligominer (Beliveau et al, 2018) and Bowtie2 (Langmead & Salzberg, 2012) against the 6.0-DD axolotl genome (Nowoshilow et al, 2018; Smith et al, 2019) (http://probegenerator.herokuapp.com/).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the involvement of nerves in regulating this process remains unknown, and the molecular mechanism is also widely unknown. There are some classic reports about regeneration (or lack of regeneration) in other internal organs, such as in the intestine (Grubb, 1975; O'Steen, 1958), pronephric duct (Howland, 1926), lung (Jensen et al, 2021), and kidney (Scadding & Liversage, 1974). For regeneration in these organs, the molecular mechanisms are widely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to understand the regeneration capacity of internal organs, Jensen et al, studied the regenerative capacity of the axolotl lung. 4 By characterizing cell proliferation in a number of cell types following injury at the distal tip of the lung, the authors found that increased proliferation was equal throughout the injured lung suggesting an organ-wide response to injury. In limb regeneration, while proliferation has also been documented to occur at more distant sites, 5 it is more focused at the site of injury compared to in lung regeneration.…”
mentioning
confidence: 99%